Analysis of childhood leukemia mortality trends in Brazil, from 1980 to 2010 - Franciane F. Silva; Eliana Zandonade; Glaucia P. Zouain‐Figueiredo (Jornal de Pediatria (Versão em Português), 2014)
Objective: Leukemias comprise the most common group of cancers in children and adolescents. Studies conducted in other countries and Brazil have observed a decrease in their mortality. This study aimed to evaluate the trend of mortality from leukemia in children under 19 years of age in Brazil, from 1980 to 2010. Methods: This was an ecological study, using retrospective time series data from the Mortality Information System, from 1980 to 2010. Calculations of mortality rates were performed, including gross, gender‐specific, and age‐based. For trend analysis, linear and semi‐log regression models were used. The significance level was 5%. Results: Mortality rates for lymphoid and myeloid leukemias presented a growth trend, with the exception of lymphoid leukemia among children under 4 years of age (percentage decrease: 1.21% annually), while in the sub‐group “Other types of leukemia”, a downward trend was observed. Overall, mortality from leukemia tended to increase for boys and girls, especially in the age groups 10‐14 years (annual percentage increase of 1.23% for males and 1.28% for females) and 15‐19 years (annual percentage increase of 1.40% for males and 1.62% for females). Conclusions: The results for leukemia generally corroborate the results of other similar studies. A detailed analysis by subgroup of leukemia, age, and gender revealed no trends shown in other studies, thus indicating special requirements for each variable in the analysis.